Sentence reductions and recidivism: lessons from the Bastille Day quasi experiment - Eric Maurin; Aurelie Ouss (Institute for the Study of Labor (IZA), 2009)
This paper exploits the collective pardon granted to individuals incarcerated in French prisons on the 14th of July, 1996 (Bastille Day) to identify the effect of collective sentence reductions on recidivism. The collective pardon generated a very significant discontinuity in the relationship between the number of weeks of sentence reduction granted to inmates and their prospective date of release. We show that the same discontinuity exists in the relationship between recidivism probability five years after the release and prospective date of release. Overall, the Bastille Day quasi experiment suggests that collective sentence reductions increase recidivism and do not represent a cost-effective way to reduce incarceration rates or prisons' overcrowding.
urn:nbn:de:101:1-20090304456
Keywords: K42; 330; Crime; prison; deterrence effect; recidivism; Straffreiheit; Kriminalität; Kriminalpolitik; Frankreich